An Open Online Course with Accessability Features - Rizzardini, R.; Chang, Vanessa; Guetl, Christian; Amado-Salvatierra, H. (AACE, 2013)
Many universities are contemplating offering online courses in an open environment.This paper describes the early experiences of massive open online courses. One such experiencewas from Galileo University in Guatemala where open online courses was offered as early as 2005.Based on this experience and responding to two major European reports, Galileo Universitydeveloped an open online course that incorporate accessibility features. What this means is that thecourse will not only teach participants to develop a website incorporating accessibility features butthe online course itself will enable participants with disabilities to participate in the course. Thissituation has motivated us to initiate research to ensure that knowledge is transferred and thelearning activities are accessible by all ‘able’ and ‘disable’ participants. This paper outlines theexperimentation setup and report on the MOOC experience. Some initial results and findings arealso discussed.